Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Menggunakan Variabel Moderasi Struktur Modal Pada Perusahaan yang Terdaftar di BEI - Mochammad Hafizh Maulana; Mu’minatus Sholichah (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of Profitability, Liquidity, and Firm Size on Firm Value Using Moderating Variables of Capital Structure in Companies Listed on the IDX. . This study uses a quantitative method that uses secondary data in the form of a complete company report. The sample in this study obtained 46 samples of companies in the health, technology, transportation, and food and beverage sectors using purposive sampling technique. The data analysis technique used is using multiple linear regression with the help of SPSS 25 software. The results show that profitability (ROE) has no effect on firm value, liquidity (CR) affects firm value, size (SIZE) affects firm value, structure capital (DER) has no effect on the relationship between ROE and PBV, capital structure (DER) has no effect on the relationship between CR and PBV, capital structure (SIZE) has no effect on the relationship between CR and PBV.